Immune-epigenetic crosstalk in haematological malignancies - Wong, Hera; Sugimura, Ryohichi (Frontiers in Cell and Developmental Biology, 2023)
Haematological malignancies comprise a diverse set of lymphoid and myeloid neoplasms which can arise during any stage of haematopoiesis in the bone marrow. Accumulating evidence suggests that chronic inflammation generated by inflammatory cytokines secreted by tumour and the tumour-associated cells within the bone marrow microenvironment initiates signalling pathways in malignant cells, resulting in activation of master transcription factors including Smads, STAT3, and NF-κB which confer cancer stem cell phenotypes and drive disease progression. Deciphering the molecular mechanisms for how immune cells interact with malignant cells to induce such epigenetic modifications, specifically DNA methylation, histone modification, expression of miRNAs and lnRNAs to perturbate haematopoiesis could provide new avenues for developing novel targeted therapies for haematological malignancies. Here, the complex positive and negative feedback loops involved in inflammatory cytokine-induced cancer stem cell generation and drug resistance are reviewed to highlight the clinical importance of immune-epigenetic crosstalk in haematological malignancies.